Crystallization-driven microstructure changes during microphase separation for environment-friendly thermoplastic triblock copolymer elastomers. (9th January 2020) - Ding, Shuangshuang; Fang, Chu; Wang, Xuehui; Wang, Zhigang
Abstract: A study on the crystallization-driven microstructure changes during microphase separation for a series of high transparent semicrystalline thermoplastic triblock copolymer elastomers (TBCPEs), polylactide- b -polyisoprene- b -polylactide (PLA- b -PI- b -PLA) was conducted in this work. A series of PLA- b -PI- b -PLA TBCPEs with different molecular masses of PI midblock and same molecular mass of PLA end blocks were synthesized. Differential scanning calorimetry was applied to demonstrate the microphase separation and crystallization behaviors of these samples. Small-angle X-ray scattering and ultra-small-angle X-ray scattering techniques were employed to investigate the different microphase-separated structures between solvent-cast and melt quenched PLA- b -PI- b -PLA films. It was disclosed that crystallization of the PLA end blocks could obviously enlarge the interdomain distance if the microphase-separated structures in PLA- b -PI- b -PLA took lamella or cylinder formats, while much less effect was noticed if the structures took sphere format. Wide-angle X-ray diffraction measurement demonstrated that PLA end blocks in PLA- b -PI- b -PLA could crystallize and eventually form α -form crystals with relatively high crystallinity values. The α -form crystals stay clear with high transparency even with high crystallinity values, because the initially formed microphase-separated structures could confine crystallization of PLA end blocks, preventing the growth of any large PLA crystals eventually. Graphical abstract: Image 1 Highlights: A series of PLA- b -PI- b -PLA TBCPEs were synthesized via RAFT polymerization. Solvent-cast and melting-quenching were separately applied to prepare the crystallized and amorphous TBCPEs. Crystallization of PLA increases the interdomain distance by one time larger than that for the amorphous one. The crystal lamellae of PLA are nano-sized, which ensures high transparency for the TBCPEs.